2003
DOI: 10.1038/sj.bjc.6601131
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the interaction between ZD1839 (‘Iressa’) and cisplatin/5-fluorouracil

Abstract: ZD1839 ('Iressa'), an orally active, selective epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, is currently being investigated in clinical trials as a treatment for cancer. 'Iressa' is a trademark of the AstraZeneca group of companies. We have previously demonstrated a synergistic interaction between ZD1839 and cisplatin/5-fluorouracil (5FU) in CAL33, a human head and neck cancer cell line that markedly expresses EGFR. This study examined the effects of this drug combination on the cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 21 publications
4
51
0
Order By: Relevance
“…All the experiments of gefitinib-induced cytotoxicity were evaluated after 3 days of continuous exposure, therefore the use of FCS in the in vitro culture system was required to ensure cell vitality; this is consistent with other studies (Magne et al, 2003;Tortora et al, 2003;Xu et al, 2003b). Furthermore, we have previously shown the stability of the drug in the presence of serum in the HPLC system .…”
Section: Resultssupporting
confidence: 86%
“…All the experiments of gefitinib-induced cytotoxicity were evaluated after 3 days of continuous exposure, therefore the use of FCS in the in vitro culture system was required to ensure cell vitality; this is consistent with other studies (Magne et al, 2003;Tortora et al, 2003;Xu et al, 2003b). Furthermore, we have previously shown the stability of the drug in the presence of serum in the HPLC system .…”
Section: Resultssupporting
confidence: 86%
“…4,5 Some phase I and II clinical trials have reported that gefitinib monotherapy does not show any benefit for the treatment of advanced breast cancer patients. 5,6 In addition, although some studies of combination therapies involving gefitinib and other cytotoxic drugs have been reported, [7][8][9][10][11] the clinical benefits remain unclear, and little information has been obtained. On the other hand, taxane shows excellent efficacy for breast cancer either as a monotherapy or in combination with other cytotoxic drugs, such as anthracycline agents.…”
mentioning
confidence: 99%
“…8,9 For breast cancer in particular, Giardiello et al reported that gefitinib enhances the taxane activity on bcl-2-overexpressing MCF7/ADR cells. 7 They demonstrated the combination effect of gefitinib and taxane, 7 but it remains unclear whether the effect is an additive or synergistic one.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Gefitinib is a well-known molecular targeting agent for epidermal growth factor (EGF) receptor (EGFR) tyrosine kinase, associated with its ligand, EGF, as well as transforming growth factor-alpha (TGF-a). Gefitinib has demonstrated antitumor activity through the effects on proliferation, apoptosis-induction [6][7][8][9] and neovascularization. 10 Intermittent NK4-expressing gene therapy rather than continuous administration of the NK4 recombinant protein has the advantage of reducing both the patient burden and medical costs.…”
mentioning
confidence: 99%